Estudio microbiológico de lactosuero de las industrias queseras del cantón Mejía de la provincia de Pichincha. - Guerrero Cabrera, Martha Lucía (2017)
Whey has a nutritional value especially protein that is used as raw material to generate products of interest for the human being. In Ecuador most of this product is discarded without proper use, according to the nutritional characteristics that it possesses, while in other countries are being produced dairy drinks based on this product that is obtained from the production of fresh cheese. In the country there is little research on the hygienic and sanitary quality of this by-product, for this reason this study was based on the microbiological analysis of the whey of small and medium-sized cheese industries of cantón Mejía to determine if the whey is suitable for the elaboration of other food by-products. Twenty samples were taken from cheesemakers, a survey was also conducted to preserve information on; the liters of processed milk, handling, quantity and treatment of whey. The results of this investigation determined the presence of microorganisms as; Streptococcus spp, mesophilic aerobes, Listeria monocytogenes, Listeria spp, E. coli, Bacillus cereus, Salmonella spp, the analyzed samples of whey exceed the limit allowed by INEN standard for liquid whey 2011. In the case of samples taken from the hands of the operatives found; Streptococcus spp, Bacillus cereus, E. coli. The study also established that one of the predisposing factors to whey contamination is that dairy companies do not meet the GMPs for dairy foods.